Older patients’ perceived burdens of their health problems: a cross-sectional analysis in 74 German general practices - Junius-Walker, Ulrike (Patient Prefer Adherence, 2015)
BACKGROUND: Older patients often experience the burden of multiple health problems. Physicians need to consider them to arrive at a holistic treatment plan. Yet, it has not been systematically investigated as to which personal burdens ensue from certain health conditions. OBJECTIVE: The objective of this study is to examine older patients’ perceived burden of their health problems. PATIENTS AND METHODS: The study presents a cross-sectional analysis in 74 German general practices; 836 patients, 72 years and older (mean 79±4.4), rated the burden of each health problem disclosed by a comprehensive geriatric assessment. Patients rated each burden using three components: importance, emotional impact, and impact on daily activities. Cluster analyses were performed to define patterns in the rating of these components of burden. In a multilevel logistic regression analysis, independent factors that predict high and low burden were explored. RESULTS: Patients had a median of eleven health problems and rated the burden of altogether 8,900 health problems. Four clusters provided a good clustering structure. Two clusters describe a high burden, and a further two, a low burden. Patients attributed a high burden to social and psychological health problems (especially being a caregiver: odds ratio [OR] 10.4, 95% confidence interval [CI] 4.4–24.4), to specific symptoms (eg, claudication: OR 2.3, 95% CI 1.3–4.0; pain: OR 2.3, 95% CI 1.6–3.1), and physical disabilities. Patients rated a comparatively low burden for most of their medical findings, for cognitive impairment, and lifestyle issues (eg, hypertension: OR 0.2, 95% CI 0.2–0.3). CONCLUSION: The patients experienced a relatively greater burden for physical disabilities, mood, or social issues than for diseases themselves. Physicians should interpret these burdens in the individual context and consider them in their treatment planning.